2013
DOI: 10.1017/s0022029912000702
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofCSN1S1gene polymorphism and stage of lactation on milk yield and composition of extensively reared goats

Abstract: The effect of CSN1S1 genotype and lactation stage on milk yield and composition were investigated in 80 extensively reared goats. Milk yield was recorded in early, mid and late lactation and individual milk samples were collected to determine: fat, protein, lactose and casein content, pH, freezing point, somatic cell count (SCC) and total microbic mesophilic count (TMC). Relative casein composition and amino acid profile were quantified by HPLC. Fatty acid profile was measured by gas-chromatography. Genotype d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…For milk yield and composition, an investigation of the Sarda breed showed that CSN1S1 BB goats produced significantly higher protein and casein percentages. In addition, αs1-CN was significantly higher in BB and AB Sarda goats than in AF and BF Sarda goats (Balia, 2013). Dominant effects were found for some genotypes for milk yield (AN and BN), fat yield (AN and BE), protein yield (AN and BE), lactose yield (AN), and TS yield (AN).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…For milk yield and composition, an investigation of the Sarda breed showed that CSN1S1 BB goats produced significantly higher protein and casein percentages. In addition, αs1-CN was significantly higher in BB and AB Sarda goats than in AF and BF Sarda goats (Balia, 2013). Dominant effects were found for some genotypes for milk yield (AN and BN), fat yield (AN and BE), protein yield (AN and BE), lactose yield (AN), and TS yield (AN).…”
Section: Introductionmentioning
confidence: 87%
“…The effects of age and lactation length on milk composition should depend on negative correlation with yield and contents of milk. Balia et al (2013) pointed out that goats with BB genotypes of the CSN1S1 gene produced higher protein and casein percentages. Unlike the findings of Balia et al (2013), B1 and B2 alleles of the CSN1S1 gene did not affect milk yield and composition in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Zullo et al [25] reported effects of the CSN1S1 genotype on milk composition in Cilentana goats. Chilliard et al [26] and Balia et al [27] have also proposed that milk fat composition is modulated by the CSN1S1 genotype. A global effect of CSN1S1 variation on protein content might be explained by the fact that CSN1S1 plays a pivotal role in casein transportation from the endoplasmic reticulum to the Golgi complex in mammary epithelial cells [28].…”
Section: Candidate Genes For Dairy Traitsmentioning
confidence: 99%